Creative Economy-Based Empowerment Pattern of Muslim Communities and Its Implications for Welfare in Lampung Province - Fatonah; Yudha, Gesit Yudha; Fadhila Faiqoh (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to analyze the creative economy process and the empowerment pattern of the Muslim community through the development of creative economy tourism in Lampung Province. The research method uses a descriptive field study. Primary data sources are obtained through in-depth interviews, direct observation, and Focus Group Discussions (FGD). Informants were selected purposively as many as 8 people consisting of relevant government officials, Muslim creative economy business actors, workers or employees, and community leaders. The results of the study show that the pattern of government empowerment in the development of the creative economy in Lampung Province is supported by two main factors, namely institutional support and infrastructure. The local government plays a role in creating a conducive ecosystem through licensing, mentoring, access to capital, incentives, and policy deregulation, which is strengthened by the role of banking and communities. The empowerment of the Muslim community is carried out in stages and participatory through improving the quality of human resources, expanding financing, strengthening institutions, and protecting businesses. The process of awareness, training, mentoring, and evaluation encourages independence, innovation, and improving welfare. The impact is seen in increasing income, skills, preserving local culture, strengthening the value of togetherness, and increasing regional competitiveness in a sustainable manner.